(untitled) - Siklos, Pierre L (New York, 2002)
This book explores their evolution since World War II in 20 industrial countries. The study considers the mix of economic, political, and institutional forces that have affected central bank behavior and its relationship with government. The analysis reconciles vastly different views about the role of central banks in the making of economic policies.
Keywords: Banks and banking, central,Monetary policy; History,History